Investigating Everyday Musical Interaction During COVID-19: An Experimental Procedure for Exploring Collaborative Playlist Engagement - Harris, Ilana; Cross, Ian (Frontiers in Psychology, 2021)
Musical Group Interaction (MGI) has been found to promote prosocial tendencies, including empathy, across various populations. However, experimental study is lacking in respect of effects of everyday forms of musical engagement on prosocial tendencies, as well as whether key aspects—such as physical co-presence of MGI participants—are necessary to enhance prosocial tendencies. We developed an experimental procedure in order to study online engagement with collaborative playlists and to investigate socio-cognitive components of prosocial tendencies expected to increase as a consequence of engagement. We aimed to determine whether mere perceived presence of a partner during playlist-making could elicit observable correlates of social processing implicated in both MGI and prosocial behaviors more generally and identify the potential roles of demographic, musical, and inter-individual differences. Preliminary results suggest that for younger individuals, some of the social processes involved in joint music-making and implicated in empathic processes are likely to be elicited even by an assumption of virtual co-presence. In addition, individual differences in styles of listening behavior may mediate the effects of mere perceived partner presence on recognition memory.